Analysis of Competition between Two Social Network Services in Korea – Facebook and Instagram - Choi, Jong You; Park, Jinsoo (International Journal of Advanced Science and Technology, 2019)
Background/Objectives: The purpose of this study is to analyze the competitive relationship between Facebook and Instagram, which have the highest daily active users (DAU) in the Korean social network services (SNS) market.Methods/Statistical analysis: We used the Lotka-Volterra (LV) equation to model the competitive relationship between the two social network service platforms. The historical DAU data of Facebook and Instagram for 1002 days from October 1, 2016 to June 29, 2019 used in the study was collected from APP APE, a mobile market analysis service.In order to analyze the variability of the competitive relationship, we divided the DAU data into four periods.Findings: We used the LV model to estimate the competition parameters between the two social network service platforms in all separated periods. In the first period, there was no relationship between two groups. In the second period, anammensalism relationship was derived in whichInstagram wasdamaged by Facebook. In the third period, a commensalism relationship created inwhich Instagram gains a unilateral benefit from Facebook.In the last period, the relationship ofmutualismis generatedin which they are mutually beneficial in the same social network market. In this study, we found that the sum of Facebook and Instagram DAU decreases.To confirm that, we did a simple comparison with Twitter and Line in the same SNS market. As a result, the decrease in the sum of Facebook and Instagram DAU is not caused by internal factors but by external factors.Improvements/Applications: Most of the research related to SNS dealt with aqualitativeanalysis. However, in this study, we conductedboth quantitative analysis and qualitative analysis on the competition between SNS platforms. Keywords: Competitive Relationship, Lotka-Volterra model, Social Network Service, Facebook, Instagram, Daily Active Users